超高齢者の頰粘膜部に発症したエナメル上皮癌の1例 - 伊藤, 泰隆; 橋本, 和彦; 田中, 陽一; 野村, 武史; 有坂, 岳大; 佐藤, 一道 (日本口腔外科学会雑誌, 2019)
We describe our experience with case of secondary peripheral ameloblastic carcinoma in a very elderly patient. The patient was a 94-year-old man who became aware of discomfort in his right cheek and was seen at the referring doctor’s clinic in late May 2017. He presented at this department for detailed evaluation and treatment the same month. We found a 40 × 20 mm mass in the right buccal mucosa. On biopsy, a diagnosis of extraosseous/peripheral ameloblastoma was established. Subsequently, the patient underwent tumor resection in July 2017. The histopathological diagnosis was secondary peripheral ameloblastic carcinoma. One year and five months have passed since the operation, and there is no evidence of recurrence or metastasis.